2016
DOI: 10.1186/s12934-016-0543-2
|View full text |Cite
|
Sign up to set email alerts
|

Highly active promoters and native secretion signals for protein production during extremely low growth rates in Aspergillus niger

Abstract: BackgroundThe filamentous ascomycete Aspergillus niger is used in many industrial processes for the production of enzymes and organic acids by batch and fed-batch cultivation. An alternative technique is continuous cultivation, which promises improved yield and optimized pipeline efficiency.ResultsIn this work, we have used perfusion (retentostat) cultivation to validate two promoters that are suitable for A. niger continuous cultivation of industrially relevant products. Firstly, promoters of genes encoding e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…When both strains were cultivated in microtiter plates, a peak in luciferase activity between 40–50 h of cultivation was observed for both strains, whereby strain NP6.4 showed about 6-fold higher expression levels compared to strain PK2.9, thus clearly demonstrating that the anafp promoter is under control of CreA (Fig 3A). Note that the observed peak-like temporal expression pattern is in good agreement with the anafp expression profile observed for retentostat cultivations (see above and [35]). We also generated reporter strain PK1.22, in which expression of the fluorescent protein eYFP was put under control of the anafp promoter.…”
Section: Resultssupporting
confidence: 86%
“…When both strains were cultivated in microtiter plates, a peak in luciferase activity between 40–50 h of cultivation was observed for both strains, whereby strain NP6.4 showed about 6-fold higher expression levels compared to strain PK2.9, thus clearly demonstrating that the anafp promoter is under control of CreA (Fig 3A). Note that the observed peak-like temporal expression pattern is in good agreement with the anafp expression profile observed for retentostat cultivations (see above and [35]). We also generated reporter strain PK1.22, in which expression of the fluorescent protein eYFP was put under control of the anafp promoter.…”
Section: Resultssupporting
confidence: 86%
“…This hypothesis is supported by publications from others who demonstrated that asexual sporulation of A. nidulans is accompanied by autolytic and apoptotic processes [ 53 , 54 , 55 , 56 ]. It is also in agreement with the observation that there is a considerable delay between induction of anafp gene expression and detection of AnAFP in the culture supernatant of A. niger [ 44 , 57 ]. Some AFPs (e.g., PAFB from P. chrysogenum and AFPB from P. digitatum ) even remained undetectable in the medium although their encoding genes were transcribed at high levels [ 13 , 37 ].…”
Section: Gene Regulation Of Afp-encoding Genes: From the General Tsupporting
confidence: 91%
“…The protein of Xyn10A had several similar homologs (> 70%) when blasted against the NCBI database ( http://www.ncbi.nlm.nih.gov ), however, it was firstly reported in this study as a high thermostable GH10 xylanase with an optimal temperature of 90 °C in Aspergillus species. It will be suitable for adding this thermostable GH10 xylanase into enzyme cocktails by expressing it in an efficient protein expression system of A. niger (Wanka et al 2016 ) or other industrial strains like T. reesei . If being considered, the potential of this enzyme still could be increased, such as enhancing the stability at high temperatures (> 80 °C), or improving the xylanase activity at low temperatures to make this enzyme work efficiently in a wide range of temperatures.…”
Section: Discussionmentioning
confidence: 99%